International workshop on biotechnology in agriculture : evolving a research agenda for the ICGEB, September, 17-22, 1985 - Natesh, S.; Chopra, V. L.; Ramachandran, S., 1934- (New Delhi : Oxford & IBH Pub. Co., 1987)
On plant molecular biology and biotechnology.
Includes bibliographies.
Keywords: Plant biotechnology -- Congresses; Agricultural biotechnology -- Congresses